Defining and Classifying Learning Outcomes: A case study - Gonçalves, Maria José Angélico (2013)
Bologne came to globalize education in higher education, creating a unified architecture that potentiates higher education and enhances the continued interconnection of the spaces of education policy in higher education in the world, in particular in Europe. The aim of this work consists in the presentation of an identification model and skills’ classification and learning outcomes, based on the official documents of the course units (syllabus and assessment components) of a course of Higher Education. We are aware that the adoption of this model by different institutions, will contribute to interoperability learning outcomes, thus enhancing the mobility of teachers and students in the EHEA (European Higher Education Area) and third countries.